Peptides from white and red meat of yellowfin tuna (Thunnus albacares): A comparative evaluation - Parvathy, U.; Binsi, P. K.; Zynudheen, A. A.; Ninan, George; Murthy, L. N. (Indian Journal of Fisheries, 2018)
Dark muscle from yellowfin tuna is rich in proteins and is an important byproduct from tuna cannery. However, it has a low market realisation and is currently utilised for preparation of fertilisers and animal feeds. Recovery and utilisation of this biomass to bioactive protein hydrolysate is a promising alternative as it facilitates food and pharmaceutical applications. However, the extent to which the properties of the hydrolysate vary in red meat derived-hydrolysate is less investigated. Hence the current study was aimed at exploring the characteristics of protein hydrolysates derived from red meat of yellowfin tuna (Thunnus albacares) in comparison to its white meat. Protein hydrolysate was prepared using 1% (w/w) papain for one hour at optimised temperature of 60°C and pH of 6.5 from white and red meat of yellowfin tuna to derive tuna white meat protein hydrolysate (TWPH) and tuna red meat protein hydrolysate (TRPH), respectively. Nutritional evaluation of tuna meat indicated comparable protein content in both white and red portions with a value of 25.99±0.24% and 24.03±0.11%, respectively and a recovery of 50.34% from white meat and 44.67% from red meat protein to their hydrolysate forms was observed. Comparative evaluation of the functional as well as bioactive properties of hydrolysates from white and red meat of tuna indicated better antioxidative activity for TWPH. However, except oil absorption capacity (OAC), functional properties viz., protein solubility, foaming capacity and emulsifying properties were higher for TRPH. Present study explores the application potential of tuna red meat to its bioactive peptides for food and pharmaceutical sectors.